2018
DOI: 10.1093/annonc/mdy072
|View full text |Cite
|
Sign up to set email alerts
|

Adding abiraterone or docetaxel to long-term hormone therapy for prostate cancer: directly randomised data from the STAMPEDE multi-arm, multi-stage platform protocol

Abstract: BackgroundAdding abiraterone acetate with prednisolone (AAP) or docetaxel with prednisolone (DocP) to standard-of-care (SOC) each improved survival in systemic therapy for advanced or metastatic prostate cancer: evaluation of drug efficacy: a multi-arm multi-stage platform randomised controlled protocol recruiting patients with high-risk locally advanced or metastatic PCa starting long-term androgen deprivation therapy (ADT). The protocol provides the only direct, randomised comparative data of SOC + AAP versu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
169
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(184 citation statements)
references
References 25 publications
4
169
0
5
Order By: Relevance
“…Other treatments may also become viable options after the completion of randomized phase 3 trials, such as enzalutamide (NCT02446405) or apalutamide (NCT02489318). The STAMPEDE study provides some comparison between abiraterone and docetaxel in this setting . The STAMPEDE trial was designed to compare different intervention arms to standard of care (ADT alone at the time).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other treatments may also become viable options after the completion of randomized phase 3 trials, such as enzalutamide (NCT02446405) or apalutamide (NCT02489318). The STAMPEDE study provides some comparison between abiraterone and docetaxel in this setting . The STAMPEDE trial was designed to compare different intervention arms to standard of care (ADT alone at the time).…”
Section: Discussionmentioning
confidence: 99%
“…More recently, the use of abiraterone acetate and prednisone with ADT in the early castration‐sensitive setting was also shown to improve overall survival in the LATITUDE and STAMPEDE (Arm G) phase III clinical trials. There have been no prospective clinical trials comparing docetaxel and abiraterone in this setting, although some analyses show similar efficacy . However, this does not take into account challenges encountered when delivering chemotherapy in a real‐world setting.…”
Section: Introductionmentioning
confidence: 99%
“…This was confirmed by the STAMPEDE study showing that ADT plus abiraterone and prednisolone was associated with significantly higher rates of overall and failure‐free survival than ADT alone among men with locally advanced or metastatic prostate cancer . Comparative analysis of chemohormonal therapy vs ADT plus abiraterone and prednisolone from the STAMPEDE study showed comparable OS and prostate cancer‐specific survival .…”
Section: Management Of Castration‐naïve Prostate Cancermentioning
confidence: 72%
“…The STAMPEDE trial also compared abiraterone acetate and docetaxel in patients with mHSPC and showed no evidence of a difference in overall or prostate cancer-specific survival, or other important outcomes such as symptomatic skeletal events. The worst toxicity grade was similar but comprised different toxicities in line with the known properties of the drugs [34].…”
Section: Metastatic Hormone-sensitive Prostate Cancermentioning
confidence: 86%